MEMPROGRAMKAN AKSES PEMBIAYAAN SYARIAH BAGI USAHA MIKRO KECIL DAN MENENGAH DI DESA KIARA PANDAK, KECAMATAN SUKAJAYA, KABUPATEN BOGOR - Tubagus Rifqy Thantawi; Miftakhul Anwar; Muhammad Parid Dudin (SAHID DEVELOPMENT JOURNAL, 2022)
Micro, Small and Medium Enterprises (MSMEs) are currently the focus of attention from the government and the general public because they have an important role in economic growth. However, MSMEs still feel and experience the difficulty of obtaining Islamic financing from Islamic banks and from Islamic microfinance institutions. This is of course also becoming more difficult for MSMEs in rural areas, including Kiara Pandak Village, Sukajaya District, Bogor Regency. Therefore, in community service activities, the introduction of sharia financing is programmed, especially for MSMEs. Access to sharia financing is included in the matters explained in the introduction of sharia financing. The community service activities which were carried out from July to August 2019 received good attention and appreciation from the community, especially Kiara Pandak Village, Sukajaya District, Bogor Regency.